A theoretical model for an encyclopaedic dictionary for the Gabonese languages with reference to Yilumbu - Saphou-Bivigat, Gilles (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DLitt (Afrikaans and Dutch))--University of Stellenbosch, 2010.